Pengembangan Sektor Pariwisata di Kabupaten Belitung: Persepsi Wisatawan - Devi Valeriani; Aning Kesuma Putri (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2020)
Tourism has the potential to be developed into a leading sector in Belitung Regency. The development of tourism is indicated by the increasing number of tourists, both domestic and foreign tourists from 2015 to 2018 by 85.9% over 4 years. This research aims to determine the gap between the level of satisfaction and the importance of supporting components of tourism to tourists who visited tourist destinations in Belitung Regency. This research was quantitative research using Importance Performance Analysis. Primary data obtained by interview through the Likert scale questions. The subjects in this research were 400 domestic tourists and 400 foreign tourists. The subjects were selected using Slovin's Formula sampling techniques. Tourism support components consisting of prices, physical facilities (infrastructures), and guarantees (services) were used to determine tourist perceptions about the level of satisfaction and importance. The results of the research showed that domestic tourists were dissatisfied with component 1) guarantees (services) consisting of cultural attractions, public communication and services officers, as well as 2) physical facilities (infrastructures) consisting of souvenir galleries, toilets, environmental cleanliness, restaurant cleanliness, and safety facilities. While foreign tourists have a low level of satisfaction with the service of the officers and the public in terms of communicating in foreign languages, cultural attractions, and environmental cleanliness.